Mediterranean and temperate treelines are controlled by different environmental drivers. (6th March 2016) - Piper, Frida I.; Viñegla, Benjamín; Linares, Juan C.; Camarero, J. Julio; Cavieres, Lohengrin A.; Fajardo, Alex
Summary: The growth limitation hypothesis (GLH) is the most accepted explanation for treeline formation, but it has been scarcely examined in Mediterranean regions, where treelines are located at lower elevations than in temperate regions. The GLH states that low temperature is the ultimate environmental driver for treeline formation, constraining C‐sinks (i.e. tissue formation) more than C‐sources. The GLH predicts similar or increasing (but not decreasing) non‐structural carbohydrate (NSC) concentrations with elevation throughout the course of the growing season. We hypothesized that elevational trends in growth and NSC in Mediterranean regions are not determined by low temperature alone. We tested the GLH by examining the mean annual basal area and NSC concentrations in developing (new twigs) and ripened tissues (branch, stem) of trees growing at three elevations in three Mediterranean and three temperate treelines in the Chilean southern Andes (33° S, Kageneckia angustifolia ; 36, 40 and 46° S, Nothofagus pumilio ) and in Spain (36° N, Pinus sylvestris ; 42° N, Pinus uncinata ). Samples for NSC were taken at the onset of summer and autumn, which represent periods of contrasting drought intensities in Mediterranean regions. Tree growth decreased significantly with elevation in temperate treelines but not in Mediterranean treelines. In Mediterranean treelines, new twig NSC concentrations increased significantly with elevation in the early summer but not in the early autumn. In temperate treelines, in contrast, no elevational or seasonal variation (or interaction between them) was observed in new twig NSC concentrations. The NSC concentrations of the branches and stems from both climates showed no elevational trends. The soluble sugars' NSC fraction increased over the season in Mediterranean treelines and decreased in temperate treelines. Synthesis . Although we found support for the growth limitation hypothesis (GLH) in temperate and Mediterranean treelines, our study shows that the tree growth and C balance in Mediterranean treelines are not controlled by low temperature alone. We suggest that environmental factors other than temperature explain the lower global elevation of Mediterranean treelines when compared to temperate treelines. Abstract : The decrease in temperature with increasing elevation is thought to be the ultimate cause of treeline formation, by limiting tree growth and controlling carbon balance. By assessing mean annual tree growth and non‐structural carbohydrate concentrations, we show that the environmental control on tree growth and C balance along elevational gradients differs between Mediterranean and temperate regions.